Humankind and the environment: an anatomy of surprise and ignorance - Faber, Malte; Manstetten, Reiner; Proops, John L. R. (Environmental values, 1992)
This paper addresses the problem of ‘ignorance’ in philosophy and science, particularly with respect to the conceptualization, study and solution of environmental problems. We begin by distinguishing between ‘risk’, ‘uncertainty’ and ‘ignorance’. We then offer a categorization of ignorance, and use these categories to assess the role of science as a means of reducing ignorance. We note that to proceed with science, several 'acts of faith' are necessary. We conclude with a discussion of the importance of an attitude of openness in science and philosophy, especially regarding environmental problems. Throughout, we illustrate our discussion of ignorance, and the problems involved in its reduction, by reference to environmental issues.